Aortic Dissection that Presented to a Tertiary Hospital’s ED in Dubai, UAE: A Descriptive Study with Literature Review - Ivyan Kambal; Esra AlHamadani; Sania Zia; Rand Aboelkher; Firas AlNajjar (Dubai Medical Journal)
Objectives: Aortic dissection is a life-threatening condition, with a high mortality rate. It can be classified into Stanford type A or type B. This study reports the clinical presentation, risk factors, systolic blood pressure, and the mortality rate of patients with confirmed aortic dissection on computed tomography (CT) imaging. Mortality rate on weekends, weekdays, daytime, and night-time were also reported.